Smart Parasitic Nematodes Use Multifaceted Strategies to Parasitize Plants - Ali, Muhammad A.; Azeem, Farrukh; Li, Hongjie; Bohlmann, Holger (Frontiers in Plant Science, 2017)
Abstract Nematodes are omnipresent in nature including many species which are parasitic to plants and cause enormous economic losses in various crops. During the process of parasitism, sedentary phytonematodes use their stylet to secrete effector proteins into the plant cells to induce the development of specialized feeding structures. These effectors are used by the nematodes to develop compatible interactions with plants, partly by mimicking the expression of host genes. Intensive research is going on to investigate the molecular function of these effector proteins in the plants. In this review, we have summarized which physiological and molecular changes occur when endoparasitic nematodes invade the plant roots and how they develop a successful interaction with plants using the effector proteins. We have also mentioned the host genes which are induced by the nematodes for a compatible interaction. Additionally, we discuss how nematodes modulate the reactive oxygen species (ROS) and RNA silencing pathways in addition to post-translational modifications in their own favour for successful parasitism in plants.